Labor Protection in the Perspective of Artificial Intelligence: New Challenges for the EU and the ILO - Sirokha, Dmytro; Volynets, Vladyslav; Kovalenko, Ruslan; Pohorielova, Oleksandra; Tkachuk, Anzhelika (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2024)
The introduction of artificial intelligence (hereinafter referred to as AI) is an active process and today touches almost all areas of human life. Laborrelations are no exception. However, the current legislation on many labor relations issues is not ready for such innovations and needs to be updated. This isa particular challenge for such participants in international relations as the ILO and the EU, as they implement national standards that are unified by many countries. The purpose of the article is to study the current challenges for the ILO and the EU with regard to AI implementation in labor relations, to classify them and to find legal solutions. The authors propose new legislative initiatives, including standardization, establishing the right to appeal against AI decisions, ensuring transparency of algorithms, enshrining the right to disconnect, and amendments to the GDPR. The practical significance of the article lies in its recommendations for improving the current legislation as guidelines for the ILO, the EU and the United States.